PENGARUH CURRENT RATIO DAN RETURN ON ASSETS TERHADAP NILAI PERUSAHAAN (PBV) PADA PT. ASTRA INTERNASIONAL Tbk. PERIODE 2013-2023 - Eka Pramesty, Ceachilia; Muhammad Luthfi, Asep (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to examine whether or not the influence of Current Ratio (CR) and Return On Assets (ROA) on Company Value (PBV) at PT Astra International Tbk for the period 2013-2023 both partially and simultaneously. This type of research is quantitative with associative technique. Analysis method used is descriptive statistics, classical assumption test, hypothesis testing (t test and F test) with a significant level of 0.05 (5%) and the data source used is secondary data. The population in this study is the financial statement data of PT Astra International Tbk for the period 2013-202. The data analysis used in this research is multiple linear regression using the Statistcal Package Social Science (SPSS) version 25.0 program. The results of this study indicate that partially Current Ratio (CR) has a significant effect on Firm Value (PBV), this is evidenced by (t test) that the tcount (-2.846)> ttable (2.306) and shows a significance value of 0.022 where 0.022 <0.05. Partially Return On Assets (ROA) has no significant effect on Firm Value (PBV), this is evidenced by (t test) that the tcount value (-1.651) > ttable (2.306) then shows a significance value greater than α, namely 0.137 > 0.05. Then simultaneously with (f test) that the value of Fcount 6.004> Ftable 4.46 then shows the significance value of 0.026 <0.05, it can be concluded that Current Ratio (CR) and Return On Assets (ROA) simultaneously have a significant effect on Company Value (PBV) at PT Astra International Tbk for the period 2013-2024.